Cultivation of Seagrapes (Caulerpa lentillifera) in Controlled Containers with the Addition of Different Doses of Fertilizers - Astuti, Nur Anggraeni; Cokrowati, Nunik; Mukhlis, Alis (Journal of Coastal and Ocean Sciences, 2021)
Caulerpa sp. is a type of seaweed from the Chlorophyceae class. Caulerpa sp. consumed as vegetables and fresh vegetables in tropical Pacific regions, especially in the Philippines and Indonesia. Caulerpa sp. contains nutrients including protein, carbohydrates, water content, crude fibre content and antioxidants. Caulerpa sp. potential as food, cosmetics and drugs. This study aims to analyze the effect of NPK fertilizer addition on Caulerpa sp. cultivation in controlled media and to analyze the best dosage. The research method used was an experimental method with a completely randomized design (CRD). The treatment tested was the concentration of fertilizer using different fertilizer concentrations, namely treatment 1 was the concentration of NPK 0 mg / L (control), treatment 2 was the concentration of NPK 20 mg / L, treatment 3 was the concentration of NPK 40 mg / L and treatment 4 was the concentration NPK 60 mg / L. The results of this study are the absolute growth rate of treatment A of -64 g, B of -71.75 g, C of -63.75 g and D of -66.5 g. The specific growth for treatment A is -3.07 %, treatment B is -3.71 %, treatment C is -3.02 % while treatment D is -3.39 %. The antioxidant content of treatment A with a value of 33.72%, treatment B with a value of 38.69%, treatment C with a value of 32.51%, treatment D with a value of 35.15%. The conclusion of this study is the addition of NPK fertilizer in this study affects the growth of Caulerpa lentillifera, by giving the effect of reducing growth